Characterization of emissions and residues from simulations of the Deepwater Horizon surface oil burns. Issue 1 (15th April 2017) - Gullett, Brian K.; Aurell, Johanna; Holder, Amara; Mitchell, William; Greenwell, Dale; Hays, Michael; Conmy, Robyn; Tabor, Dennis; Preston, William; George, Ingrid; Abrahamson, Joseph P.; Vander Wal, Randy; et al.
Abstract: The surface oil burns conducted by the U.S. Coast Guard from April to July 2010 during the Deepwater Horizon disaster in the Gulf of Mexico were simulated by small scale burns to characterize the pollutants, determine emission factors, and gather particulate matter for subsequent toxicity testing. A representative crude oil was burned in ocean-salinity seawater, and emissions were collected from the plume by means of a crane-suspended sampling platform. Emissions included particulate matter, aromatic hydrocarbons, polychlorinated dibenzodioxins/dibenzofurans, elements, and others, the sum of which accounted for over 92% by mass of the combustion products. The unburned oil mass was 29% of the original crude oil mass, significantly higher than typically reported. Analysis of alkanes, elements, and PAHs in the floating residual oil and water accounted for over 51% of the gathered mass. These emission factors, along with toxicity data, will be important toward examining impacts of future spill burning operations. Graphical abstract: Highlights: The purposeful, at-sea burns during the Deepwater Horizon disaster were simulated. Emissions were sampled for a wide variety of pollutant types. Over 92% of the combustion products were accounted for. Over 51% of the oily residue was identified.